Integrasi Personal Balanced Scorecard, Psikologi Integral, dan Positive Organization Behaviour/ Scholarship sebagai Pendekatan Komprehensif di Perusahaan/Organisasi - Nurlaila Effendy (Buletin Psikologi, 2016)
The performance of an organization exists when each individual and team in the organization have productivities. The performance of an organization is commonly measured based on its tangible assets, i.e .: physical assets and financial capital. The performance of tangible assets depends on intagible assets (such as : image of company, brand, data base, and human resources). Intagible asseets are key factors to development of an organization. In this respect, an integrated system is a determinant to the performance of an organization. An integrated approach among Personal Balance Scorecard, Positive Organizational Scholarship, Positive Organizational Behavior and Integral Psychology will definitely strengthen the performance of an organization, and each organization has opportunities to develop as a positive organization. Each individual in an organization has vitality and experiences flows, while each organization may go flourishing.